A NEGLECTED AREA OF ACCOUNTING VALUATION. - Hord, Warner H. (The Accounting Review, 1942)
A business unit is one of the thousands of temporary storage tanks through which capital flows in the circulatory system by which it gives economic life to the nation. The current flood of literature and the numerous disagreements and contradictions with respect to what are accounting principles make one hesitate to attempt another such statement and suspicious of the reception such as attempt may receive. This article will deal only with a skeleton outline of what the author believes to be the more basic accounting principles underlying and, therefore, controlling the operation of the bookkeeping mechanics as a means of discovering and analyzing what appear to be the causes for the existence of a neglected area of accounting valuation. Double entry is based upon the concept of duality of a single business property. This duality is created through the separation of business properties from their actual owners by placing these properties in the possession of a fictitious business entity, which holds and operates such properties under an assumed trust arrangement between the business entity and the legal owners.